The significance of medical history and its impact on the early diagnosis of inborn errors of immunity - Marta Mazalon; Elżbieta Grześk; Anna Dąbrowska; Anna Urbańczyk; Sylwia Kołtan (Termedia Publishing House, 2024)
Inborn errors of immunity (IEI) are genetically determined disorders which present clinically as increased susceptibility to infectious, autoinflammatory, or autoimmune diseases, potentially leading to fatal outcomes. Some doctors omit collecting family history, an element of the examination that allows for initial risk stratification of the disease and permits further detailed diagnostics. Currently, unfortunately, the role of medical history is downplayed by primary care physicians in favour of diagnostic tests. The availability of genetic tests in most countries is low, so we would like to use examples to emphasise the enormity of the role of anamnesis, the simplest part of the patient's examination. The medical history provided valuable information that raised suspicions of IEI. Consequently, genetic studies were conducted for meticulous diagnoses, and then the most effective treatments were administered, including pre-emptive haematopoietic stem cell transplantation.